2021
DOI: 10.1155/2021/3694664
|View full text |Cite|
|
Sign up to set email alerts
|

Application of the Artificial Neural Network in the Diagnosis of Infantile Bronchial Bridge with 64-Slice Multislice Spiral CT

Abstract: The objective is to study the application of spiral CT in the diagnosis of the trachea in children. In this study, the effect of 64-slice multislice spiral CT in diagnosing infant bronchial bridge was studied based on an artificial neural network. From June 2020 to December 2020, 100 cases of children with the trachea in the outpatient department of our hospital were selected as the research object. They were divided into the study group and the control group, with 50 cases in each group. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, the diagnostic efficacy of these biomarkers remains unsatisfactory due to their varying specificity and sensitivity. In light of this, artificial neural networks (ANNs) have emerged as powerful tools for predictive analysis of both tumor and non-tumor diseases (26,27). The utilization of machine learning in the identification of tumor biomarkers has garnered remarkable advantages as another tool (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnostic efficacy of these biomarkers remains unsatisfactory due to their varying specificity and sensitivity. In light of this, artificial neural networks (ANNs) have emerged as powerful tools for predictive analysis of both tumor and non-tumor diseases (26,27). The utilization of machine learning in the identification of tumor biomarkers has garnered remarkable advantages as another tool (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%